Older adults’ experiences with using information and communication technology and tech support services in New York City: findings and recommendations for post-pandemic digital pedagogy for older adults - Finkelstein, Ruth; Wu, Yiyi; Brennan-Ing, Mark (Frontiers in Psychology, 2023)
Although Information and Communication Technology (ICT) has great potential to help people to cope with challenges associated with aging, the intended benefits of ICT are not always realized in this population due to access barriers and low digital literacy. As the COVID crisis accelerated ICT application into so many aspects of life, defining and supplying adequate tech training and support to older adults has become a matter of unprecedented urgency. During the pandemic, numerous tech support initiatives for older adults got underway; evaluation of the effectiveness of these initiatives is more unusual. This research partnered with a large, multi-service organization in New York City who gave some groups of clients ICT devices, unlimited broadband, and access to technology training in response to COVID lockdowns. This study investigates patterns of adoption and use and older adults' experiences with ICT support services. This work may better inform the existing and emerging tech training and support for older adults beyond COVID-19. Data were obtained from interviewer-administered surveys of 35 older adult recipients of ICT devices, connectivity, and training in New York City. The average age was 74 years (range = 55 to 90 years). The group was diverse regarding race/ethnicity (Black 29%, Latino 19%, White 43%). All had low incomes and participated in at least one older adult program. Surveys consisted of multiple-choice items and open-ended responses. We learned that one size does not fit all when it comes to ICT training and support for older adults. Findings support the conclusion that customized training based on individuals’ skills rather than age are needed, and suggest that service organizations include assessment of ICT access and use into other standard intake protocols. While connection to devices and services certainly brought positive outcomes to these older adults’ lives, the newly learned skills did not always translate to exploration of potential new benefits of ICTs. Therefore, tech support training should start by understanding an individual’s interests and needs and incorporating tech education to help them identify a wide range of existing and emerging online services that could help them meet these needs.